A liberdade da vontade e o problema da condição de possibilidade da responsabilização jurídica: um estudo da posição de Kant em contraposição à crítica de Schopenhauer - Waldir Severiano de Medeiros Júnior (2016)
This study aims to examine, first, Immanuel Kant's position on the issue of freedom of the will as a condition of legal imputability. Then, seeks to analyze the criticism of Arthur Schopenhauer to the way what Kant postulated, in his practical philosophy, freedom of the will as the condition of possibility of legal imputability. According to Schopenhauer, a relative practical freedom, translated into intellectually determinable will, and not an absolute practical freedom, translated into free will (transcendental autonomy), is what would be the true enabler of state imputability, whence his conclusion in the sense that it is the potential of change of the agents behavior, with not the culpability, the main factor that the society and the State should be concerned. This means, finally, that, according to Schopenhauer, an alternative and deterministic conception as his, contrary to what is often said, does not compromise, but enhances imputability.